THE FORECAST OF THE FREIGHT CARS NUMBER - Senko, V. I.; Hurskyi, Ye. P. (Science and Transport Progress, 2008)
Performing the increasing amount of transportations under guaranteed safety of the train traffic is the most important priority for Belorussian railway. To do so, it is necessary to provide the transportation process with a modern, reliable rolling stock. At present this problem, related firstly to the ageing of freight wagon stock, is acute enough for Belorussian railway and has need for its quickest solution. For development of the efficient strategy of recovery and renovation of the rolling stock the great importance has a scientifically justified forecast of the working stock. A mathematical model of the forecast of working stock of freight-wagons is developed and its design values for a period till 2012 are obtained, which are taken into account and used in development of the business plan of the railway operation till 2010.